Interpersonal motor resonance in autism spectrum disorder: evidence against a global “mirror system” deficit - Enticott, Peter; Kennedy, Hayley; Rinehart, Nicole J.; Bradshaw, John; Tonge, Bruce; Daskalakis, Zafiris J.; Fitzgerald, Paul (Frontiers in Human Neuroscience, 2013)
The mirror neuron hypothesis of autism is highly controversial, in part because there are conflicting reports as to whether putative indices of mirror system activity are actually deficient in autism spectrum disorder (ASD). Recent evidence suggests that a typical putative mirror system response may be seen in people with an ASD when there is a degree of social relevance to the visual stimuli used to elicit that response. Individuals with ASD (n = 32) and matched neurotypical controls (n = 32) completed a transcranial magnetic stimulation (TMS) experiment in which the left primary motor cortex was stimulated during the observation of static hands, individual (i.e., one person) hand actions, and interactive (i.e., two person) hand actions. Motor-evoked potentials (MEP) were recorded from the contralateral first dorsal interosseous, and used to generate an index of interpersonal motor resonance (IMR; a putative measure of mirror system activity) during action observation. There was no difference between ASD and NT groups in the level of IMR during the observation of these actions. These findings provide evidence against a global mirror system deficit in ASD, and this evidence appears to extend beyond stimuli that have social relevance. Attentional and visual processing influences may be important for understanding the apparent role of IMR in the pathophysiology of ASD.